Ballistic and physical properties of highly fractured alumina - Horsfall, Ian; Edwards, Michael R.; Hallas, M. J. (Maney Publishing, 2010)
It is known that ceramic materials in armour are often shattered by a penetrating projectile and the resistance to penetration is therefore dependent upon the properties of this failed material. A small explosive charge was used to shatter a confined 95% alumina tile by passing the stress wave from an explosive detonation through a steel cover plate and into the ceramic. This fractured material was shown to have an elastic modulus of 130 GPa compared to 330 GPa for the monolithic alumina. Impact indentation tests and ballistic depth of penetration tests were performed on the intact ceramic, shattered ceramic and a pressed ceramic powder compact. It was found that the fractured material had a ballistic efficiency approximately 70% of that of the monolithic alumina and was also able to cause significant erosion to the project